PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 005 SUNGAI PINANG KECAMATAN KUBU - Nizla Yanti; Zariul Antosa; Lazim N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The background of this research is the process of learning andteaching fourth grade Pinang River State 005 Kubu district in science subjects arestill didomonasi by the teacher so that students become passive, as well asmaterials provided by the teacher and the learning outcomes are not satisfactorywith an average value below KKM. This study aims to determine whether or notthe influence of inquiry learning model, both individually and classical to class IVstudent learning outcomes in science subjects Pinang River Elementary School005 Kubu district. This study was conducted on 25 students. Data were collectedthrough observation using the observation sheet to the data model of inquirylearning through UAS I and UAS II for learning outcomes data. The results of thestudents increased in the first cycle compared to prior to the action or beforePTK, as for the improvement of learning outcomes that occurred before and afterthe PTK held the first cycle an increase of 20% in the first cycle is completestudent for 14 people with 56% completeness. While on the second cycle therewas an increase of 32% with the thoroughness of the students were 22 people witha completeness of 88%. While the activities of the students at the first meeting ofthe first cycle of 35%, the second meeting by 60% and the second cycle at the firstmeeting by 70%, the second meeting is 95%. So, between the first cycle andsecond cycle an increase of 25%. From the research and discussion as it has beendescribed above that the use of inquiry learning model is correct then theactivities and outcomes of student learning is enhanced and better. Thisinformation proved that the hypothesis which says: With Application LearningModel of inquiry can improve science learning outcomes Elementary Schoolfourth grade students 005 Pinang River Kubu district.Keywords: Inquiry Learning Model, Results Learning IPA